Strategi Marketing Public Relations untuk Meningkatkan Kunjungan Wisatawan di Kota Bandar Lampung - Sakinah, Shalwa; Kartika, Tina; Besar, Ibrahim (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
This article discusses the Marketing Public Relations strategy of the Bandar Lampung City Tourism Office in increasing Bandar Lampung City Tourist Visits because the number of domestic tourists experienced an insignificant increase of 4.05% and foreign tourists experienced a decrease of 2.15%. This condition makes the Bandar Lampung City Tourism Office as the implementing element of regional autonomy have responsibility for tourism, one of which is visiting tourists from Bandar Lampung City. This research uses the analysis of Philip Kotler and Kevin Lane Keller's Marketing Public Relations strategy theory. The qualitative analysis method was used to achieve the research objectives, namely the Marketing Public Relations strategy of the Bandar Lampung City Tourism Office. Findings in research by the Bandar Lampung City Tourism Office in increasing tourist interest using 6 Marketing Public Relations strategies such as publications, events, news, speeches, social activities and identity media.